PENGARUH LATIHAN LEMPAR SHUTTELCOCK TERHADAP KEMAMPUAN PUKULAN LOB PADA PEMAIN BULUTANGKIS PB BUNGO SPORT KABUPATEN BUNGO - Saputra, Deddy Rahmat (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research started from the existence of several problems including the inaccuracy of choosing models and forms of training in achieving the desired goals and targets, especially increasing the ability of lob shots and the unknown effect of shuttlecock throwing exercises on increasing the ability of lob strokes in PB Bungo Sport Badminton Players in Bungo Regency. This study aims to determine the effect of the shuttlecock throwing exercise on increasing the lob ability of badminton athletes in PB. Bungo Sport Bungo Regency. This type of research is an experiment with the design of